Lo spazio analogico dell’immagine : Tra Derrida e la pittura cinese - Ghilardi, Marcello (Scenari, 2021)
By intertwining some reflections by Jacques Derrida with some results of the theoretical reflection on painting in the Chinese tradition, we can get some hints and ideas emerge about an aesthetics of the process and transition, of manifestation and withdrawal of form. The practice of drawing and painting opens up a sort of “analog space”, as a place of co-implication and ex-plication of infinite relationships between the elements that compose reality and its image, or the relationship between subject and object, day and night, visible and invisible.